2016
DOI: 10.1002/jmv.24614
|View full text |Cite
|
Sign up to set email alerts
|

Oropharyngeal and laryngeal but not oral cancers are strongly associated with high‐risk human papillomavirus in 172 Greek patients

Abstract: A strong and consistent association has been reported between human papillomavirus (HPV) infection and oropharyngeal cancer, whereas a similar link has not yet been clarified in oral and laryngeal cancer. The purpose of this study was to investigate the association between HPV infection and head and neck squamous cell carcinoma (HNSCC) in Greek patients. Cytological or tissue specimens from 172 cases patients with HNSCC and cytological specimens from 91 control subjects were analyzed for HPV DNA detection and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…In our cohort, the overall HPV DNA prevalence was 13.6%, with HPV 16 being the predominant genotype. This is comparable with previous studies where overall HPV DNA prevalence in LSCC was 13.5% . However, Xu et al reported a markedly lower HPV infection rate than in our current study, which is only 4.9%.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our cohort, the overall HPV DNA prevalence was 13.6%, with HPV 16 being the predominant genotype. This is comparable with previous studies where overall HPV DNA prevalence in LSCC was 13.5% . However, Xu et al reported a markedly lower HPV infection rate than in our current study, which is only 4.9%.…”
Section: Discussionsupporting
confidence: 89%
“…TA B L E 2 Clinicopathological characteristics of patients and cell cycle-related proteins In our cohort, the overall HPV DNA prevalence was 13.6%, with HPV 16 being the predominant genotype. This is comparable with previous studies where overall HPV DNA prevalence in LSCC was 13.5% 11,13. However, Xu et al14 reported a markedly lower HPV…”
supporting
confidence: 90%
“…HPV infection has been shown to cause oropharyngeal cancer. The association between HPV and LSCC is based on the morphological similarities between the cervical and the squamous epithelium, as well as the detection of the commonest oncogenic HPV genotypes (HPV-16, HPV-18) in both cervical and laryngeal cancers (LC) [10,11]. However, the clinical significance of HPV infection remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Laryngeal cancer can result from the combined action of smoking, drinking, air pollution, HPV infection and sex hormone levels. Recently, increasing studies have found that among the many pathogenic factors of laryngeal cancer, high-risk HPV (HR-HPV) infection may be one of the most important 2, 3. Epidemiological studies reported HPV infection rates in laryngeal cancer ranging from 8% to 83% 3, 4; a meta-analysis showed a 28% HPV infection rate in all LSCC 3, and HPV infection was correlated with its occurrence 5.…”
Section: Introductionmentioning
confidence: 99%